Some Remarks on Bernardo Segni’s Translation of Ethica Nicomachea - Cufalo, Domenico (Literatūra, 2022)
In the middle of the sixteenth century, Bernardo Segni (Florence, 1504 – Florence, 1588) published some Italian translations with commentaries on some works of Aristotle. He was not a scholar nor did he have a university affiliation nor could he boast a deep knowledge of Greek language, but he worked in the cultural climate of Duke of the Florentine Republic Cosimo I (Florence, 1519 – Florence, 1574) and of the Florentine Academy, whose aim was to raise the cultural centrality of Florence and its dialect. In this paper I analyze some passages of his translation and commentary on Aristotle’s Ethica Nicomachea (Florence 1550; reprint Venice 1551). Through this examination some characteristics of the author’s work emerge, such as his didactic purposes, which may be related to the type of his audience, his (poor) knowledge of classical authors and sources, and his tendency towards continuous dialogue with the present.